2014
DOI: 10.1093/ehjci/jeu162
|View full text |Cite
|
Sign up to set email alerts
|

A revised methodology for aortic-valvar complex calcium quantification for transcatheter aortic valve implantation

Abstract: Both leaflet and LVOT calcium are significant predictors of PVL and exert an important synergistic influence on this complication, even in appropriately sized valves. With careful attention to thresholds for detection, clinically relevant leaflet calcium volumes can be identified with either non-contrast or contrast CT scans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
95
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 152 publications
(97 citation statements)
references
References 16 publications
1
95
1
Order By: Relevance
“…Severe aortic valve calcification and oversizing were shown to be an independent predictor of PVL after SE-and BE-TAVR in prior studies. 5,7,20 In the present study, use of SE valve for elliptic annuli resulted in lower device success rates, but increased oversizing of SE valves resulted in higher device success rates, whereas the degree of BE valve oversizing had little effect on device success rate (Figure 3). On ROC curve analysis, lower oversizing of SE valves for elliptic annulus predicted unsuccessful device implantation.…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation
“…Severe aortic valve calcification and oversizing were shown to be an independent predictor of PVL after SE-and BE-TAVR in prior studies. 5,7,20 In the present study, use of SE valve for elliptic annuli resulted in lower device success rates, but increased oversizing of SE valves resulted in higher device success rates, whereas the degree of BE valve oversizing had little effect on device success rate (Figure 3). On ROC curve analysis, lower oversizing of SE valves for elliptic annulus predicted unsuccessful device implantation.…”
Section: Discussionmentioning
confidence: 47%
“…A recently validated 850-HU threshold was used to detect areas of calcium in the region of interest. 5 All aortic annulus measurements were performed by a dedicated CT core laboratory at CedarsSinai Heart Institute before TAVR.…”
mentioning
confidence: 99%
“…It was previously found to be associated with increased PVL or PD rates, and annulus injury only following BE-THV implantations. [7][8][9]11,12) Previous studies also demonstrated that there is reduced rates of PVL or PD following XT compared to CV TAVI. [4][5][6] Most of these previous studies included different grades of aortic valve calcification but did not evaluate association with DLZ calcification.…”
Section: Discussionmentioning
confidence: 99%
“…A recently validated 850 Hounsfield unit threshold was used to detect areas of calcium in the region of interest. 8) The decision to proceed with TAVI was with the consensus of a dedicated heart team including experienced clinical and interventional cardiologists and cardiovascular surgeons. Transthoracic echocardiography was performed after TAVI at 30-days.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation